Pengaruh Personal Identity, Social Identity, Kredibilitas Influencer Terhadap Green Purchasing Behavior - Merin Adelin Ena; Dimas Angga Negoro (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research tests and analyzes personal identity, social identity, influencer credibility on green purchasing behavior. And knowing which variables are the most dominant in influencing green purchasing behavior. The research uses a quantitative approach that uses causal relationships. The sample selection criteria in this study were aged 12 years to 43 years who had purchased and used Tisoo brand tissue and were in the Jabodetabek area. Questionnaires were collected from 100 respondens, the data was then processed using the multiple linear regression method. Based on the results of the analysis, it is known that the personal identity variable partially has a positive effect on green purchasing behavior. Meanwhile, the social identity variable and the influencer credibility variable partially have a negative effect on green purchasing behavior. Simultaneous hypothesis testing states that personal identity, social identity and influencer credibility have a positive effect on green purchasing behavior. and the most dominant variable in influencing green purchasing decisions is the personal identity variable. The implication is that companies like Tisoo should emphasize environmental values in their marketing and select influencers who understand eco-friendly products to encourage green purchasing.